Model Anteseden Kinerja Pegawai: Peran Kepuasan Kerja dan Motivasi pada Unit PBJ Provinsi Jawa Timur - Rahayu, Rita Noviyanti; Fikri, Amir; Maria, Maya (Jurnal Samudra Ekonomi dan Bisnis, 2026)
This study analyzes the influence of workload, compensation, and work environment on employee performance in the Goods/Services Procurement Work Unit (UKPBJ) of East Java Province, with job satisfaction as a mediating variable and motivation as a moderating variable. The study used a quantitative explanatory approach with data collected from 90 respondents. The research model analysis used Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4 software. The results obtained indicate that workload, compensation, and work environment have a positive and significant effect on employee performance. However, motivation does not moderate the relationship between workload, compensation, and work environment on employee performance. Job satisfaction significantly mediates the influence of the work environment on employee performance. These findings emphasize the importance of managing work demands and strengthening organizational resources in improving employee performance in public sector procurement institutions.